Indoor Air Quality Issues for Rocky Mountain West Tribes - Webb, Logan; Sleeth, Darrah K.; Handy, Rod; Stenberg, Jared; Schaefer, Camie; Collingwood, Scott C. (Frontiers in Public Health, 2021)
Native American populations face considerable health disparities, especially among those who live on reservations, where access to healthcare, education, and safe housing can be limited. Previous research on tribal housing has raised concerns about housing construction, damage, and possible linkage to adverse health effects (e.g., asthma). This community-based participatory research (CBPR) project investigated indoor air quality issues on two Rocky Mountain west reservations. At the onset of the project, the research team formed a partnership with community advisory boards (CABs) consisting of representatives from tribal councils and community members. Research design, implementation, and dissemination all took place in full collaboration with the CABs following approval through official tribal resolutions. Residential homes were monitored for particulate matter with diameter <2.5 microns (PM2.5) and radon concentrations. Low-cost air quality sensors and activated charcoal radon test kits were placed in tribal households for 6-8 days. A large amount of data were below the sensor limit of quantification (LOQ), but several homes had daily averages that exceeded suggested PM2.5 guidelines, suggestive of the potential for high exposure. Additionally, nearly half of all homes sampled had radon levels above the EPA action level, with mitigation activities initiated for the most concerning homes. Findings from this study indicate the need for future community-wide assessments to determine the magnitude and patterns of indoor air quality issues.